Compensation Management and Employee’s Work Commitment in the Kwara State Internal Revenue Service, Ilorin, Nigeria. - Emmanuel Olaniyi Dunmade (Indonesian Journal Of Business And Economics, 2020)
The study examines the effect of compensation management on the employee’s work commitment in the Kwara State Internal Revenue Service (KW–IRS), Ilorin, Nigeria. Stratified random sampling technique was utilized for the study with the administration of structured questionnaire to the respondents so as to elicit the required information. The data generated was analyzed with regression analysis with aid of SPSS, (V. 22.0). Findings showed that compensation management is a positive and significant predictor of employee’s work commitment in the Kwara State Internal Revenue Service. The study concluded that organizations that effectively and efficiently manage its compensation policy, in respect to employee’s commitment, will outperforms those organizations that do not. Thus, the study recommends the organization should be more innovative and effective in the management of compensation policies, so as to focus more on the adequate welfare for the employees and as well treating them as the most precious assets of the establishment.The study examines the effect of compensation management on the employee’s work commitment in the Kwara State Internal Revenue Service (KW–IRS), Ilorin, Nigeria. Stratified random sampling technique was utilized for the study with the administration of structured questionnaire to the respondents so as to elicit the required information. The data generated was analyzed with regression analysis with aid of SPSS, (V. 22.0). Findings showed that compensation management is a positive and significant predictor of employee’s work commitment in the Kwara State Internal Revenue Service. The study concluded that organizations that effectively and efficiently manage its compensation policy, in respect to employee’s commitment, will outperforms those organizations that do not. Thus, the study recommends the organization should be more innovative and effective in the management of compensation policies, so as to focus more on the adequate welfare for the employees and as well treating them as the most precious assets of the establishment.